2016
DOI: 10.1001/jamapsychiatry.2016.2387
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Hormonal Contraception With Depression

Abstract: Use of hormonal contraception, especially among adolescents, was associated with subsequent use of antidepressants and a first diagnosis of depression, suggesting depression as a potential adverse effect of hormonal contraceptive use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
414
7
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 484 publications
(459 citation statements)
references
References 46 publications
28
414
7
10
Order By: Relevance
“…However a recently published Danish nationwide prospective cohort study reported a significant association between CHC use and depression. The study followed over 1.06 million women aged 15–34 years with no prior diagnosis of depression 331. Compared with non-users, current users of COC had a RR of first use of an antidepressant of 1.23 (95% CI 1.22–1.25), users of a CTP (RR 2.0; 95% CI 1.76–2.18) and users of a CVR (etonogestrel) (RR 1.6; 95% CI 1.55–1.69).…”
Section: Side Effects Associated With Chc Usementioning
confidence: 99%
“…However a recently published Danish nationwide prospective cohort study reported a significant association between CHC use and depression. The study followed over 1.06 million women aged 15–34 years with no prior diagnosis of depression 331. Compared with non-users, current users of COC had a RR of first use of an antidepressant of 1.23 (95% CI 1.22–1.25), users of a CTP (RR 2.0; 95% CI 1.76–2.18) and users of a CVR (etonogestrel) (RR 1.6; 95% CI 1.55–1.69).…”
Section: Side Effects Associated With Chc Usementioning
confidence: 99%
“…Although most women do not have onset of psychiatric symptoms with modern contraceptives,61 whether women who have a history of mood disorder are more sensitive to oral contraceptives remains controversial, as some reviews have suggested an increased risk of mood destabilization whereas others have not 6162. A nationwide prospective study of 1 061 997 women found that oral contraceptive users had higher rates of first diagnosis of depression (rate ratio 1.1, 95% confidence interval 1.08 to 1.14) and antidepressant treatment (1.23, 1.22 to 1.25) compared with non-users63; consequently, psychiatric response to oral contraceptives should be considered in postpartum women who are starting to use them. The 2016 United States Medical Eligibility Criteria for Contraceptive Use recommendation is that women use progesterone-only contraceptives rather than combined progesterone and estrogen preparations in the early postpartum period of up to 42 days and consider duration post partum and breastfeeding status when changing to preparations containing estrogen 64.…”
Section: Personalized Treatment For Specific Clinical Characteristicsmentioning
confidence: 99%
“…Based on this concept, it is reasonable to antagonize and/or to remove endotoxin when treating patients with sepsis [52,53]. Unfortunately, clinical trials focused on antagonizing a single mediator, such as LPS, TNF-α, IL-1β, and TLR4, did not show any promising results [54]. …”
Section: Endotoxin Removal By Extracorporeal Therapiesmentioning
confidence: 99%